(untitled) (Research, Society and Development, 2022)
Geoprocessing, especially geotechnologies and especially remote sensing, are widely used to monitor vegetation cover and water content present, through two indices of vegetation and continental waters. The objective of this research is to analyze the changes that occurred in vegetation cover for periods with different rainfall intensities, through two vegetation indices NDVI and NDWI, in the years 2014 and 2015 in the semi-arid region of the municipality of Patos-PB, using satellite images. do Landsat 8/OLI. For the study and mapping in the area that encompasses the city of Patos - PB, a research was carried out involving the new remote sensing satellites, and within the current context of spatial, temporal and spectral evolution, it was decided to use images used by LandSAT-8/ OLI. The behavior of the distribution of rainwater, comparing the year of 2014 in Ducks with a normal climatological, referring to 30 years of recorded data (1981 to 2010), did not intuit to identify the dry and rainy period for that year. The similarity of the annual distribution of chuvas is observed for normal climatological conditions, with ressalva or more than January, bem abaixo than expected. To observe the weather, it is visible that the summer months correspond after June/July. The rainfall average at a short time of 30 days for the same space-time of 2015 was less, but in a period of 15 days, at the average of 2015 it was more significant for the recovery of vegetation.